Language Style Used in Darkest Hour Movie - Wisesa, Gede Bagus Kalpa; Sudipa, I Nengah; Rajeg, Gede Primahadi Wijaya (CV. Ulil Albab Corp, 2024)
This study examines the sociolinguistics of the language style used in the 2017 movie Darkest Hour, directed by Joe Wright and written by Anthony McCarten. The study focuses on two main research inquiries: (1) What language styles are utilised in the movie Darkest Hour (2) What variables influence the predominant language style utilised in the movie Darkest Hour. The study aims to identify and describe the language styles in the movie using Mandell and Kirszner's (2005) theory, which categorises language styles as frozen, formal, consultative, casual, and intimate. Furthermore, Holmes' (2013) theory is utilised to examine the aspects that impact the primary language style found in the movie. The study focuses on analysing characters' speech in Darkest Hour to reveal language patterns and analyse the sociolinguistic dynamics shown in the movie. This research delves into how language styles and contextual elements interact to enhance our understanding of how language is used for characterisation, narrative development, and historical representation in movie discourse.